Multi-criteria Strategic Framework for Improving Residential Buildings Operational Energy Efficiency (Case Study Damascus Residential Youth Buildings) (Damascus University Journal for engineering sciences, 2021)
The poor thermal performance of traditional residential buildings has led to residents' complaints in light of the post-war energy shortage and the increasing periods of power cuts. Therefore, improving residential building energy efficiency is a key factor in Syria post-war new housing affordability, environmental challenges and socio-economic restoration. This is due to its significant impact (building's thermal performance, energy consumption, emission, and internal environment) especially at occupancy stage, being the longest phase of the building lifecycle. Given the post-war limited resources, residential building energy efficiency requires a multiple criteria for decision making.   This study aim to assess decision-makers to start thinking backwards from the occupancy phase when deciding between energy efficient alternatives which must be made in the early design stages. The research evaluates and compares between an energy efficient building with a conventional one; in terms of differences in specifications, thermal performance, operational energy efficiency, carbon dioxide emissions, comprehensive energy exchange costs, and thermal performance modeling. The results of the study showed a significant decline in the energy and thermal performance and the emission of carbon dioxide resulting from the operational energy in the widespread traditional building compared to the energy efficient building. Hitherto, the energy-cost trade-off analysis demonstrates that the energy efficient building’s initial cost is 35% more than the traditional building with 10 years payback period. Therefore, based on the thermal performance modeling of several building envelops alternatives, the research presents a set of obstacles and recommendations. The research developed a framework of phased levels to improve the energy efficiency of youth housing buildings. The framework developed by this research includes the responsibilities of the involved parties during the four stages of: empowerment, planning and design, implementation and follow-up, and continuous improvement, in light of relying on local-efforts for reconstruction.